A fuzzy reasoning approach to assess innovation risk in ecosystems - Abreu, António (2018)
Currently, companies to be competitive must achieve high rates of innovation and respond quickly to market needs. According to a number of managers and researches innovation is crucial for companies to stay “alive." Taking into account several reports, the development of co-innovation networks based on a collaborative environment is the best strategy to support innovation projects. However, the absence of mechanisms to detect and even anticipate potential risks of innovation based on a collaborative approach is an obstacle to the proliferation of this way of working. To address this issue, this paper discusses an approach based on fuzzy reasoning for analyzing the level of risk in co-innovation projects. It is discussed how this approach can be applied to co-innovation projects within the contexto of a collaborative ecosystem. At last, it is discussed the benefits, and challenges found on experimental results from a Portuguese co-innovation network.